Avoided Crossing Phonons Realizes High‐Performance Single‐Crystalline β‐Zn4Sb3 Thermoelectrics - I‐Lun Jen; Cheng‐Yen Lin; Kuang‐Kuo Wang; Chun‐Ming Wu; Chi‐Hung Lee; Hsin‐Jay Wu (Advanced Science)
Abstract This study reveals the mechanisms behind the ultralow lattice thermal conductivity κL in β‐Zn4Sb3 single crystals through inelastic neutron scattering (INS). Analyzing phonon behaviors and the interaction between acoustic phonons and rattling modes, the first experimental evidence of avoided crossing in β‐Zn4Sb3 is provided. The rattler‐phonon avoided crossings contribute to the low κL in a β‐Zn4Sb3 single crystal, enhancing the thermoelectric figure‐of‐merit (zT). TEM characterizations of the β‐Zn4Sb3 single crystal with intrinsic and ultralow κL reveal a grain‐boundary‐free structure with uniformly dispersed rotation moiré fringes that contribute to low lattice thermal conductivity while maintaining a uniform elemental distribution. Additionally, the significant impact of crystallinity control coupled with dilute doping on boosting thermoelectric performance, with single‐crystalline single leg outperforming their polycrystalline counterparts is demonstrated. Notably, the conversion efficiency η of the undoped β‐Zn4Sb3 single leg achieves 1.4% under a temperature gradient of 200 K.